Multiscale modelling of DNA mechanics - Dršata, Tomáš; Lankaš, Filip (Journal of physics. Condensed matter, 2015)
Mechanical properties of DNA are important not only in a wide range of biological processes but also in the emerging field of DNA nanotechnology. We review some of the recent developments in modeling these properties, emphasizing the multiscale nature of the problem. Modern atomic resolution, explicit solvent molecular dynamics simulations have contributed to our understanding of DNA fine structure and conformational polymorphism. These simulations may serve as data sources to parameterize rigid base models which themselves have undergone major development. A consistent buildup of larger entities involving multiple rigid bases enables us to describe DNA at more global scales. Free energy methods to impose large strains on DNA, as well as bead models and other approaches, are also briefly discussed.
Keywords: molekulární modely; molekulární konformace; DNA; Models, Molecular; Molecular Dynamics Simulation; Molecular Conformation; simulace molekulární dynamiky; Animals; lidé; Systems Biology; Nanotechnology; systémová biologie; Humans; zvířata; nanotechnologie